#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge. (July 2022) - Hänel, Hilkje C
Two decades ago, Tarana Burke started using the phrase 'me too' to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article's concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of 'proper' sexual violence and accounts that are not 'proper' experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.